SIBERIAN CRATON - A FRAGMENT OF A PALEOPROTEROZOIC SUPERCONTINENT - Rosen O.M. (My University, 2002)
The sialic (volcanogenic) material of the terranes in 3the Siberian fragment of a Paleoproterozoic supercontinent separated from the mantle 3.5, 3.3, 3.0, and 2.5 billion years ago. The collision zones (sutures) between the terranes are dated by granitoids which melted from the crust of the terranes in two periods of time: 1.9 and 1.8 billion years ago. Local metamorphism and granite generation inside the collision (fault) zones were accompanied by synchronous areal dry granulite metamorphism in the adjacent terranes. This implies a fairly uniform field of high temperatures and pressures typical of the thicker crust of the collision prism. The amalgamation of the continental-crust fragments was terminated by the formation of a huge mountain massif ca. 1.8 billion years ago. Later, these mountains were wholly eroded. Early Riphean platform-type clastic sediments started to accumulate on the resulting peneplain 1.65 billion years ago, i. e., 150 million years after the end of the collision. The Siberian Craton is a part of the Pangea-1 Paleoproterozoic supercontinent which originated from the fragments of the broken Archean Pangea-0 supercontinent which had existed as microcontinents with their own sedimentary-volcanic covers which were transformed, after the collision, to the foldbelts superimposed over the basements of the old terranes. The exception was the Paleoproterozoic Akitkan volcanic belt which evolved first as a volcanic arc and later, in the course of the total amalgamation, was thrust over the ancient basement and involved in anorogenic acid magmatism (A-granites).
Keywords: SIBERIAN CRATON; PALEOPROTEROZOIC SUPERCONTINENT; SUTURES; EARLY RIPHEAN; Proterozoic; Archean; Paleoproterozoic; Riphean; Precambrian::Proterozoic; Докембрий::Протерозой::Рифей; Докембрий::Протерозой; Докембрий::Протерозой::Палеопротерозойская; Precambrian::Archean; Докембрий::Архей; Precambrian::Proterozoic::Paleoproterozoic; Precambrian::Proterozoic::Riphean